PrP(TSE) Distribution in a Primate Model of Variant, Sporadic, and Iatrogenic Creutzfeldt-Jakob Disease - Herzog, Christian (American Society for Microbiology, 2005)
Human prion diseases, such as Creutzfeldt-Jakob disease (CJD), are neurodegenerative and fatal. Sporadic CJD (sCJD) can be transmitted between humans through medical procedures involving highly infected organs, such as the central nervous system. However, in variant CJD (vCJD), which is due to human contamination with the bovine spongiform encephalopathy (BSE) agent, lymphoreticular tissue also harbors the transmissible spongiform encephalopathy-associated prion protein (PrP(TSE)), which poses a particularly acute risk for iatrogenic transmission. Two blood transfusion-related cases are already documented. In addition, the recent observation of PrP(TSE) in spleen and muscle in sCJD raised the possibility that peripheral PrP(TSE) is not limited to vCJD cases. We aimed to clarify the peripheral pathogenesis of human TSEs by using a nonhuman primate model which mimics human diseases. A highly sensitive enzyme-linked immunosorbent assay was adapted to the detection of extraneural PrP(TSE). We show that affected organs can be divided into two groups. The first is peripheral organs accumulating large amounts of PrP(TSE), which represent a high risk of iatrogenic transmission. This category comprises only lymphoreticular organs in the vCJD/BSE model. The second is organs with small amounts of PrP(TSE) associated with nervous structures. These are the muscles, adrenal glands, and enteric nervous system in the sporadic, iatrogenic, and variant CJD models. In contrast to the first set of organs, this low level of tissue contamination is not strain restricted and seems to be linked to secondary centrifugal spread of the agent through nerves. It might represent a risk for iatrogenic transmission, formerly underestimated despite previous reports of low rates of transmission from peripheral organs of humans to nonhuman primates (5, 10). This study provides an additional experimental basis for the classification of human organs into different risk categories and a rational re-evaluation of current risk management measures.